Challenges in intelligence analysis lessons from 1300 BCE to the present - Walton, Timothy R. 1948- (Cambridge University Press, 2010)
"In Challenges in Intelligence Analysis, Timothy Walton offers concrete, reality-based ways to improve intelligence analysis. After a brief introduction to the main concepts of analysis, he provides more than forty historical and contemporary examples that demonstrate what has, and what has not, been effective when grappling with difficult problems. The examples cover a wide span of time, going back 3,000 years. They are also global in scope and deal with a variety of political, military, economic, and social issues.Walton emphasizes the importance of critical and creative thinking and how such thinking can be enhanced. His book provides a detailed and balanced explanation of intelligence work and will be of particular interest to students who are contemplating a career in intelligence analysis"